Tujuan Pendidikan Islam dalam Pandangan Nurcholish Madjid - Safitri, Lis; Manshur, Fadlil Munawwar (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2016)
This article is a qualitative research explained by descriptive-inferential method and analyzed by method of hermeneutics of Hans George Gadamer. Nurcholish Madjid (1939-2005) had more thorough idea about the objective of Islamic education. The ultimate goal of human life is ‘abd and khalîfah. God gives emotions and fitrah to achieve it. Emotion, lead by knowledge, will bring human to the goodness or badness. ‘Abd and khalîfah has manifested in good worshiping and good in social life.